Exploring The Reasons Of Indonesian Young Adult Consumers Toward Sustainably Packaged Food & Beverages Product - Gunawan, Arie Indra; Amalia, Fatya Alty; Ramadhan, Muhamad; Bansah, Pearl Fafa (Politeknik Negeri Bandung, 2024)
Sustainable packaging in the F&B industry is now widely used and developed by companies to address climate change issues or reduce costs and increase consumer product value. However, targeted consumers do not always buy products in sustainable packaging for various unknown reasons. The originality of this study is the creativity of young adults as participants, as most researchers do not have a deeper understanding of why consumers are most likely and least likely to purchase sustainably packaged products. It is a consumer survey. In addition, this study contributes to a comprehensive understanding of young adult consumers, purchasing intent, and awareness of sustainable packaging of F&B products. The purpose of this qualitative study was to thoroughly investigate why consumers are most likely and least likely to purchase sustainable packaged F&B products. Twenty-two young adult consumers aged 18-24 were asked the open-ended questions to gain a more in-depth understanding of the topic under the study. Most participants associate sustainable packaged F&B products with price, quality, and appearance as reasons for deciding whether to buy the product. However, some participants also mentioned digital marketing efforts: social media marketing, influencer use, and trend tracking, as reasons for being involved in the product. This study suggests that companies are leveraging digital and traditional strategies to create a complete green marketing mix that reaches a broader range of customers.